VARIATION IN ONION VARIETIES FOR REACTION TO NATURAL INFECTION OF ALTERNARIA PORRI (ELLIS) CIFF. AND STEMPHYLIUM VESICARIUM (WALLR.) - BEHERA, SRUJANI; SANTRA, PALASH; CHATTOPADHYAY, SHUBHOMITA; DAS, SRIKANTA (The Bioscan, 2013)
Twenty two onion varieties were tested during 2010-2012 at Kalyani, West Bengal, for evaluating their resistance levels against A. Porri and S. vesicarium, causal agents of purple blotch and stemphylium blight diseases, respectively under field condition. Disease severity was recorded by using 5 point rating scale when the disease was developed to its maximum extent and percent disease index was calculated. None of the 22 varieties, screened against purple blotch & stemphylium blight disease, was free from the disease. There were significant variations were existed among the varieties under study. Results revealed that, only one variety viz VG-18 performed best among all the tested cultivars by displaying resistant and moderately resistance to purple blotch and stemphylium blight, respectively, while its comparative yield (288.18 q/ha) also remained at top. While three varieties viz. NRCRO-4(1168), Sel.157and COLL-652 are susceptible, varieties VG-18 and VG-19 were found moderately resistant and remaining 17 are moderately susceptible to stemphylium blight only. In case of purple blotch, only VG-18 is resistant, 12 varieties are moderately resistant and nine varieties are moderately susceptible. Total yield also affected with the increase in disease severity. Highest yield recorded in variety VG-18(288.18 q/ ha) followed by VG-19 (285.72).